Collaborative conversations in a post-graduate study group: constructing academic and professional identities - Kempe, Elspeth Michelle (My University, 2014)
There appears to be very little research into the functioning of teacher-student study groups that operate at the interface between academic and professional environments, and into the possible influences of such groups on the members’ teacher and post-graduate student identities. In particular, there appears to be no insider research into groups that are self-constituted and therefore function without the mediation of a researcher. This study is an insider investigation of the ways of talking in a self-constituted teacherstudent study group in an attempt to establish how the use of dialogic talk contributed to the co-construction of knowledge and at the same time to the constitution of identities as confident, innovative students and teachers. It takes a socio-cultural approach to learning, and draws on the theories of Vygotsky and Bakhtin which highlight the use of talk, especially dialogic talk, as a tool for learning. It draws on the work of Wenger and of Gee in the analysis of the constitution of identities as confident, innovative students and teachers, and on the concept of ‘figured worlds’, developed by Holland, Lachicotte, Skinner, & Cain, to develop an understanding of what enabled or constrained each group member’s identity/ies as a confident and innovative teacher. The data were comprised of transcripts of the conversations of study group members working together, and of two sets of interviews: the first conducted while the group members were still studying and the second two years after they had graduated. The findings show firstly, that engaging in dialogic talk while working together played an important role both in the co-construction of knowledge and in the constitution of confident student and teacher identities, and secondly, that continued professional engagement with other study group members may be significant for the on-going development of professional identities as confident teachers. The study concludes that encouraging teachers who return to study to form study and support groups, encouraging them to draw on each others’ professional knowledge as a resource during the learning process, and encouraging them to use dialogic talk as they work together, may provide some of the support needed for them to develop confidence in themselves as both students and teachers. Key words: identity, teacher-student study groups, dialogic talk, communities of practice, figured worlds, insider research.
A thesis submitted to the Wits School of Education, Faculty of Humanities, University of the Witwatersrand in fulfilment of the requirements for the degree of Doctor of Philosophy Johannesburg 2014